2021
DOI: 10.1620/tjem.254.129
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Oral Bacteria and Fungi Microbiota in Tibetan and Chinese Han Living at Different Altitude

Abstract: Knowledge about the impact of altitude and ethnicity on human oral microbiota is currently limited. To obtain the baseline of normal salivary microbiota, we analyzed the bacteria and fungi composition in Tibetan (HY group) and Han population (CD group) living at different altitudes by using next-generation sequencing (NGS) technology combined with PICRUSt and FUNGuild analyses. There were significant differences in oral microbiota composition between the two groups at phylum and genus levels. At the phylum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In high altitude areas, residents often experience dry mouth and dry tongue (36), which can be uncomfortable. Moreover, it's reported that altitude was a risk factor to oral microbiota disorders (37). An imbalance in the oral microbiota is associated with dental caries(38), periodontitis, periimplantitis, mucosal diseases, and oral cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In high altitude areas, residents often experience dry mouth and dry tongue (36), which can be uncomfortable. Moreover, it's reported that altitude was a risk factor to oral microbiota disorders (37). An imbalance in the oral microbiota is associated with dental caries(38), periodontitis, periimplantitis, mucosal diseases, and oral cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The FUNGuild database was applied to predict the nutritional and functional groups of the mycobiota [43]. It can be only classified into three main trophic modes: phagotroph, symbiotroph, saprotroph.…”
Section: Logistic Regression For Mycobiota Profilementioning
confidence: 99%
“…Second, we only used ITS1 sequencing to analyze mycobiota. Because of the limitations of FUNGuild [43], only preliminary functional prediction was performed in our study. Metagenomic detection should be considered in further study to better validate the function of the oral mycobiota from different populations.…”
Section: Logistic Regression For Mycobiota Profilementioning
confidence: 99%
“…The oral cavity is one of the earliest organs in the body to be exposed to the external environment, and its internal microbiome is more susceptible to changes due to external factors such as diet, medicines, pollutants in the environment, and geographical location ( Thomas et al, 2014 ; Dong et al, 2021 ; Gupta et al, 2022 ). Oral microbial communities are closely related to human health, affecting not only oral health but also the health of the whole body ( Gao et al, 2018 ; Zhang Y. et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%